Influence of the physiological state on the energy, protein and endocrine metabolism, in Siboney de Cuba cows - Gallego, C.; Peñalver, A.; Méndez, Mildred; Lenz Souza, María; García, R. (Cuban Journal of Agricultural Science, 2018)
A total of 56 Siboney de Cuba cows in different physiological states (lactating and dry cows) were used, with the objective of evaluating the concentrations of glucose, cholesterol, triglycerides, total proteins and insulin-like growth factor type I (IGF-I). In group I GI (n = 18) dry cows, GII (n = 22) between 45 and 60 days of lactation and GIII (n = 16) higher than 150 days of lactation. The biochemical analyzes were performed through the enzymatic calorimetric method and the readings were made by absorption spectrophotometry. The IGF-I values were obtained by radioimmunoassay. The animals from GII showed lower (P = 0.0001) concentrations of glucose (1.89 ± 0.22 mmol/L-¹) and IGF-I (P <.0001) (98.74 ± 9.85 ng / mL-¹), in relation to the dry group (3.11 ± 0.27 mmol / L-1 and 103.35 ± 11.87 ng / mL-1) and > 150 lactation days (2.78 ± 0.20 mmol / L-¹ and 186.13 ± 9.49 ng / mL-1). The lactating cows showed higher (P = 0.0011) cholesterol levels (GII = 3.69 ± 0.20 mmol / L-¹ and GIII = 3.53 ± 0.20 mmol/L-1), with respect to the GI (2.70 ± 0.25 mmol/L-¹). The GIII showed higher (P <.0001) concentrations of triglycerides (0.45 ± 0.04 mmol/L-1) and total proteins (P = 0.0087) (89.4 ± 1.8 g/l-¹) than the rest (GI = 0.26 ± 0.03 mmol/L-1 and 84.0 ± 2.2 g/l-1) (GII = 0.27 ± 0.03 mmol/L-1 and 82.8 ± 1.8 g/l-1). It is concluded that the physiological state influences on the performance of the metabolic indicators, mainly due to the demand of energy reserves, as consequences of the productive level of the animals. Key words: physiological state, ,energy, protein, endocrine metabolism